TOOLS USED IN PEDAGOGICAL TECHNOLOGIES - M.B.Aliyeva, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article analyzes the main tools used in the implementation of pedagogical technologies and their role in the educational process. The importance of verbal, nonverbal, visual, audio, and natural teaching tools is scientifically discussed. The  psychological  characteristics  of  students’  perception  of  information  are  also examined. The effectiveness of active learning methods such as lectures, round-table discussions,  and  debates  is  justified.  The  necessity  of  integrating  information technologies  into  modern  education  is  emphasized.  The  comprehensive  use  of pedagogical  tools  is  considered  an  important  factor  in  improving  the  quality  of education.